Building Prophetic Accountability in State Financial Management for the People's Welfare - Rahmat Zuhdi (Master of Accounting Universitas Trunojoyo Madura, 2022)
State/regional financial management has undergone fundamental changes since the issuance of the state finance law and its audit mechanism. The decentralized system that was built has shifted from its primary goal, namely the welfare of the people. This shift occurred with the emergence of the phenomenon that the opinion of the results of the examination of financial statements has become the ultimate goal in the management of state/regional finances which results in a reduction in the level of service to the community. This study aims to construct a critical discourse on prophetic accountability in managing state/regional finances for the community's welfare. This study uses a qualitative approach with a critical paradigm through a critical analysis of Ibn Khaldun's discourse on the ideal state. The results of this study indicate that the implementation of state/regional financial management can be achieved by a system of justice (the rule of law), responsibility (vertical and horizontal), leadership abilities (intellectual and strategic), and moral values. All of these conditions must be owned by all leaders and elements of the national organization, which ultimately results in order, social harmony, and the growth of a dynamic and conducive civilized society. So that this can be an alternative solution to provide awareness that leadership is a mandate that should offer benefits to society and nature as a form of accountability to God (Rahmatan Lil 'Aalamiin).